Aberrant expression of regulatory cytokine IL-35 in patients with systemic lupus erythematosus. (October 2015) - Cai, Z; Wong, C K; Kam, N W; Dong, J; Jiao, D; Chu, M; Lam, C W K; Tam, L S
Objective: This study characterizes an IL-35-mediated regulatory role in patients with systemic lupus erythematosus (SLE). Methods: Plasma of SLE patients and healthy controls (HCs) was analyzed for the concentrations of IL-35 and soluble gp130 by using ELISA. mRNA expression of IL-35 subunit (p35 and EBI3) and its receptor (gp130 and IL-12Rβ2) in peripheral blood mononuclear cells (PBMCs) was assessed by RT-qPCR. Flow cytometry was performed to evaluate the number of CD4 + CD25 high CD127 − Treg cells and the expression of IL-35 receptor on the CD4+ helper (Th) cells and CD19+ B cells. Plasma collected from SLE patients and HCs was assayed for cytokine and chemokine expression by Luminex multiplex assay. Results: Plasma IL-35 and soluble gp130 levels positively correlated with each other and were significantly higher in patients with severe SLE compared with HCs. Significantly higher levels of inflammatory cytokines/chemokines CCL2, CXCL8, IL-6, interferon (IFN)-γ, IL-10 and IL-17A were observed in plasma of SLE patients than HCs. mRNA levels of IL-35 and its receptor were significantly positively correlated in PBMCs from SLE patients and their levels were higher in SLE than HCs. The increase significantly correlated with changes in SLE Disease Activity Index (SLEDAI) (all p  < 0.05). In addition, the number of Treg cells in severe and moderate SLE patients were both significantly lower than HCs, where the ratio of CD4 + CD25 − effector T cell %/CD4 + CD25 high CD127 − Treg % was found to be significantly higher in severe SLE patients. Furthermore, the expression of gp130 on CD4+ Th cells and percentage of Tregs were positively correlated with each other, and both were negatively correlated with SLEDAI. Conclusion: Our findings indicate that high level of plasma IL-35 in active SLE patients expressed with low level of IL-35 receptor (gp130) on CD4+ Th cells. These data raise the possibility that the level of IL-35 expression in SLE patients is not sufficient to induce the production of CD4 + CD25 high CD127 − Tregs, and subsequently suppress the release of inflammatory cytokines and chemokines upon inflammation.